IMPLEMENTASI PROGRAM DAUROH TAHFIDZ DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SANTRI DI PONDOK PESANTREN AL MUKMIN SUKOHARJO - Hanief Abdillah Rantiono; Afiful Ikhwan; Happy Susanto (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze the implementation of the tahfidz dauroh program in improving the quality of the Qur’an memorization of students at the Al Mukmin Islamic Boarding School in Sukoharjo. The study employs a qualitative approach with a case study design to provide an in-depth description of the tahfidz program implementation process, the learning strategies applied, and the resulting quality of the students’ memorization. The research subjects included boarding school supervisors, tahfidz instructors, and students participating in the tahfidz program. Research data were obtained through observation of tahfidz learning activities, in-depth interviews, and analysis of tahfidz program documentation. Data analysis was conducted through a systematic process of data reduction, data presentation, and drawing conclusions. The research findings indicate that the implementation of the tahfidz program is carried out through structured intensive memorization activities using the talaqi, tikrar, tasmi’, and muraja’ah methods. This program is conducted in several daily sessions that allow students to increase their memorization while continuously reviewing what they have memorized. The quality of students’ memorization in this program is demonstrated through the accuracy of recitation, fluency in memorization, and the consistency of muraja’ah performed routinely. Additionally, the supportive environment of the pesantren and the guidance of tahfidz instructors are crucial factors in the program’s implementation. This study concludes that the dauroh tahfidz program contributes to improving the quality of students’ Quran memorization through intensive and structured memorization learning within the pesantren environment.